2006
DOI: 10.1523/jneurosci.1072-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Intense Isolectin-B4 Binding in Rat Dorsal Root Ganglion Neurons Distinguishes C-Fiber Nociceptors with Broad Action Potentials and High Nav1.9 Expression

Abstract: Binding to isolectin-B4 (IB4) and expression of tyrosine kinase A (trkA) (the high-affinity NGF receptor) have been used to define two different subgroups of nociceptive small dorsal root ganglion (DRG) neurons. We previously showed that only nociceptors have high trkA levels. However, information about sensory and electrophysiological properties in vivo of single identified IB4-binding neurons, and about their trkA expression levels, is lacking. IB4-positive (IB4ϩ) and small dark neurons had similar size dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
230
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(246 citation statements)
references
References 50 publications
(114 reference statements)
13
230
1
2
Order By: Relevance
“…This finding is surprising, given that Na v 1.9, a channel that is predominantly expressed in IB 4 ϩ neurons (Cummins et al 2000;Fjell et al 1999), produces a persistent inward current at rest that can acutely shift resting potential in a depolarizing direction (Baker et al 2003;Herzog et al 2001). Our data in this regard are similar to results recently reported by Fang et al (2006). One possible explanation is that, without added GTP, the Na v 1.9 persistent current is too low to effect membrane potential (Baker et al 2003).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is surprising, given that Na v 1.9, a channel that is predominantly expressed in IB 4 ϩ neurons (Cummins et al 2000;Fjell et al 1999), produces a persistent inward current at rest that can acutely shift resting potential in a depolarizing direction (Baker et al 2003;Herzog et al 2001). Our data in this regard are similar to results recently reported by Fang et al (2006). One possible explanation is that, without added GTP, the Na v 1.9 persistent current is too low to effect membrane potential (Baker et al 2003).…”
Section: Discussionsupporting
confidence: 92%
“…For our characterization of the voltage-dependent and kinetic properties of Na v 1.8 current, cells were held at Ϫ70 mV for 10 min using fluoride-based pipette solution to inactivate Na v 1.9 current (Choi et al 2006;Coste et al 2004). Because Na v 1.9 channels produce persistent currents during the depolarization pulses of 100 ms and are more heavily expressed in IB 4 ϩ than in IB 4 Ϫ cells (Fang et al 2006;Fjell et al 1999;Rush et al 2005) we estimated the extent of possible contamination of Na v 1.9 current using the ratio of maximum late current amplitude at the end of 100-ms pulses to peak current amplitude. The maximal percentage of late current amplitudes to peak current for IB 4 ϩ and IB 4 Ϫ neurons was 5.0 Ϯ 0.5 and 3.0 Ϯ 0.5%, respectively, and were significantly different (P Ͻ 0.01).…”
Section: Voltage Dependency Of Activation and Steady-state Inactivatimentioning
confidence: 99%
See 1 more Smart Citation
“…The TTXR sodium channel Nav1.9/SNS2/NaN is selectively expressed in small DRG neurons (Tate et al 1998) and is detected in nociceptive A and C fibre neurons as analysed by electrophysiology and IHC of labelled lumbar neuron in rats (Fang et al 2002). In C fibre nociceptors of lumbar DRG, Nav1.9 immunoreactivity is correlated with isolectin-B4 (IB4)-binding levels (Fang et al 2006). Expression is detected in rat L4/5 DRG by IHC at E15 for Nav1.8 and not before E17 for Nav1.9 (Benn et al 2001).…”
Section: Ion Channel Expression In Drgmentioning
confidence: 99%
“…The IB4 2ve cell fraction includes large diameter proprioceptive neurons and small diameter peptidergic nociceptors (Julius and Basbaum, 2001;Fang et al, 2006). Cell size analysis showed that the large diameter IB4 2ve cells were the principal cell types responsive to PTX.…”
Section: Discussionmentioning
confidence: 99%